Economic Effect of Covid-19 Pandemic on the Access of Birth Control Service in Health Facilities in Women of Childbearing Aged 15-49 Years - Alhamuddin Alhamuddin; Rabiatul Adwiyah; Dadang Suhenda; Rindag Ekawati; Angela Sri Meylani Wijayanti (International Journal of Business Studies, 2022)
This paper describes the effect of the economic effects of the Covid-19 pandemic on access to birth control services in health facilities for women of childbearing age (WUS) 15-49 in West Java. This type of research is a quantitative description using Bivariate, Multivariate and dichotomic / binary logistic regression analysis. The results of this study indicate that there is no significant effect simultaneously between the effects of pandemic-19 on the use of modern contraceptives and an increase in the number of pregnancies in women of reproductive age (wus) 15-49 years in West Java because the p-value is 0.233 or more. The magnitude of the alpha used is 5% (0.05).) While each variable does not have a significant partial effect on Y in the X model. The sig values ​​are more than 0.05 (alpha) used. This means that the economic effect of the COVID-19 pandemic does not have a significant partial effect on access to family planning services in health facilities for women of childbearing age 15-49 years in West Java. The dependent variable is 33.1% and there are 100% -39% = 66.9 % other factors outside the model that explain the dependent variable in this study